2018
DOI: 10.1159/000491995
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Patients Are More Sedentary and Less Physically Active than Age- and Sex-Matched Cognitively Healthy Older Adults

Abstract: Aims: The aim of this study was to examine physical activity and sedentary behaviour characteristics of ambulatory and community-dwelling patients with dementia compared to cognitively healthy age-, sex- and weight-matched controls. Methods: In this cross-sectional study, we included community-dwelling dementia patients (n = 45, age 79.6 ± 5.9 years, Mini-Mental State Examination [MMSE] 22.8 ± 3.2) and matched controls (n = 49, age 80.0 ± 7.7 years, MMSE 29.0 ± 1.2). Participants wore a wrist accelerometer for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 39 publications
8
70
2
2
Order By: Relevance
“…Indeed, there is strong epidemiological evidence suggesting a linkage of higher midlife physical activity levels and reduced AD risk later in life. Likewise, it is well documented that older adults with AD are less physically active relative to age-and sex-matched, cognitively healthy older adults [23,24]. Hence, it is likely that reduced CRF parameters in older adults with AD are at least partially attributable to reduced habitual physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is strong epidemiological evidence suggesting a linkage of higher midlife physical activity levels and reduced AD risk later in life. Likewise, it is well documented that older adults with AD are less physically active relative to age-and sex-matched, cognitively healthy older adults [23,24]. Hence, it is likely that reduced CRF parameters in older adults with AD are at least partially attributable to reduced habitual physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…A technological limitation of the current study is the manual detection of body motion used. Preferably, an automatic detection method, such as a small wearable sensor like an accelerograph [32,33], would be used.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive status is considered a predictive factor for healthy life span among older adults-especially in terms of physical activity and walking level [23][24][25]. Matsueda et al [24] reported a significant relationship between walking level and cognitive status evaluated by the MMSE among patients with hip fracture: Significant differences were observed in mean MMSE by walking status among people in their 80s (dependent walking status: 5.9 points, partially dependent walking status: 16.5 points, independent walking status: 23.7; p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%